STRATEGI GURU MENGAJARI PERILAKU BERKOMITMEN SISWA KELAS X SMK HASAEL PURU DALAM PEMBELAJARAN PENJASORKES - Kristianus Marianus Nau Nesi; Jusuf Blegur; Julian J Leko (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
This research is to describe the strategy of the teacher in behavior commitment teaching by students X vocational high school (SMK) Hasael puru on physical education learning process. There is the aim of study is to explain the strategy of teacher as the eduator on behavior commitment teaching by students physical sport education learning process. The method that used in this research is qualitative method, the technique which is used to collected the data is triangulation technique there are: documentation, interview,observation.the steps of analysing data are: reduction data, display data and verification. The triangulation data and the triangulation technique are used to test the validity of the data. The result of the study express about 6 findings there are : 1. Behavior commitment teaching, 2. The agreement and the aim of behavior commitment teaching, 3. Physical sport education learning process is to form the behavior commitment, 4. The strategy of behavior commitment teaching, 5. The manner to develop the behavior of commitment, 6. What kind of the characteric that be supposed from behavior commitment teaching